Reflective memories: The Indian diaspora who call South Africa home - Archary, Kogielam K. (HTS teologiese studies, 2022)
Durban, a coastal city in KwaZulu-Natal (one of the nine provinces in South Africa) boasts the Durban Harbour. One hundred and sixty-two years ago, this harbour was referred to as the Port of Natal. Between the year’s of 1860 and 1911, 152 184 indentured Indian labourers entered the British owned Colony of Natal through this port. Even though indentureship was officially abolished in Natal on 21 July 1911, the hardships and challenges endured by Indian nationals in Natal continued. This article shines a spotlight on the period 1895–1960 through the theoretical prism of indentureship by focusing on the reflective memories of the respondent, Mr J.S. Singh, a nonagenarian. Using oral history methodology, face-to-face interviews were held with the respondent. His reflective memories brought alive the reality of life experiences in Natal between 1895 and 1960. He shared the journey of his Indian born paternal grandmother, Mrs Takurine Mahesh Singh who constitutes the cohort that left their country of birth as Indian nationals but subsequently created the Indian diaspora in Natal, where their descendants now call South Africa their home.Contribution: The content of this article is not simply described but also briefly reflected upon and explored as certain issues may be of interest to new, emerging and established oral historians. Furthermore, audio and video recordings of the interviews, which clearly illustrate oral history as the methodology as applied in this research, are available for academic, education and research purposes.